Optimal allocation of virtual machines for cloud-based multimedia applications - Nan, Xiaoming; He, Yifeng; Guan, Ling (2012 IEEE 14th International Workshop on Multimedia Signal Processing, 2012)
With the emergence of cloud computing, cloud-based multimedia applications have been increasingly adopted in recent years. There are two major challenges for multimedia application providers: the round trip time (RTT) requirement and the resource cost. In this paper, we study the virtual machine (VM) allocation problem for multimedia application providers to minimize the resource cost under RTT requirements. Specifically, we propose the optimal VM allocation schemes for single-site cloud and multi-site cloud, respectively. Moreover, we propose the greedy algorithms to efficiently allocate VMs in each case. Simulation results demonstrate that the proposed optimal VM allocation schemes can optimally allocate VMs to achieve a minimal resource cost.